Musical abilities in professional activity of the specialist of the social and cultural sphere - Vera A. Kurina; Svetlana S. Lukasheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article presents the authors' opinion on the problem of training future specialists in the socio-cultural sphere, the relevance of which is increased in connection with the new requirements for University graduates identified in the GEF IN 3++. The practice of the educational process on the example of training students of the direction of training 51.03.03 Socio-cultural activities of the two profiles "Management of socio-cultural activities" and "Socio-cultural animation and recreation". The review of the literature on the issue of graduates ' readiness for professional activity allowed the authors to formulate the main theoretical provisions and determine the importance of musical abilities of students - future specialists in the social and cultural sphere. Theoretical analysis of psychological and pedagogical literature on the problem under study, as well as experimental work confirmed the importance of musical training of students in the direction of Socio-cultural activities, the need for the formation of their musical abilities that are needed in the implementation of various projects, activities, programs, as socio-cultural developments, projects are impossible without musical accompaniment. The musical Outlook of the specialist of the social and cultural sphere promotes development of musical culture, increase of level of professional training of graduates. The study clarified the basic concepts of "professional activity", "profession", "musical abilities". The authors described the basic skills necessary for specialists in the socio-cultural sphere; disclosed qualification requirements, employers ' requests, as well as the requirements of the GEF IN 3++ related to professional skills and abilities of future specialists in the socio-cultural sphere. The authors paid special attention to the experiments and the results of the study; the data obtained in the course of the survey of students in the field of socio-cultural activities on the importance of musical abilities for their activities are presented.